Strongyloides stercoralis infection in transplanted patients - Sadjadi, Seyed-Ali (International Scientific Literature, Inc., 2013)
PATIENT: Male, 36 FINAL DIAGNOSIS: Strongyloidiasis SYMPTOMS: Abdominal pain • anorexia • eosinophilia • fever • letargy • weight loss MEDICATION: — CLINICAL PROCEDURE: — SPECIALTY: Infectious diseases OBJECTIVE: Challenging differential diagnosis, rare disease BACKGROUND: Strongyloidiasis is a worldwide infection, infecting approximately 100 million people in more than 70 countries. It is common in Southeast Asia, Latin America, Papua New Guinea and some parts of the United States. Malnutrition, cancer, organ transplantation, hemodialysis and prolonged use of corticosteroids increase the risk of this opportunistic infection. Undiagnosed and untreated, its mortality rate can be high. CASE REPORT: We present a 36 year old Black man with history of malignant hypertension and glomerulonephritis who had chronic eosinophilia and vague, poorly localized abdominal pain and tenderness. He received three deceased donor kidney transplants, two of them failed and the third one succeeded. However, after transplantation, his abdominal pain and discomfort increased, became anorexic, lost weight and developed fever and lethargy. Duodenal aspirate examination was positive for strongyloides stercoralis. Immunosuppressant medications were discontinued and he was treated with thiabendazole. In spite of treatment, his condition deteriorated and he expired. CONCLUSIONS: Due to low sensitivity of stool and serological examinations, diagnosis of strongyloidiasis often is delayed. A high index of suspicion and prompt diagnosis and treatment are essential in decreasing the morbidity and mortality of this infection. Before organ transplantation, every attempt should be made to find the cause of peripheral blood eosinophilia and in endemic areas and among patients coming from countries where the infection is known to exist, organ recipients and donors should be screened for parasitic infections including strongyloidiasis